Analisis Faktor Biologi, Faktor Ergonomi, Faktor Elektrikal dengan Penerapan Standar K3 di Rumah Sakit Tk. II Putri Hijau Kota Medan Tahun 2025 - Elvina, Giovanni; Silaban, Gerry (Innovative: Journal Of Social Science Research, 2025)
Hospitals are workplaces with diverse potential hazards, thereby increasing the risk of occupational accidents and diseases. Managing these potential hazards can be done by implementing occupational health and safety (OHS) standards in accordance with Permenkes No. 66 Tahun 2016. This study aims to analyze the factors associated with the implementation of OHS standards among nurses at Class II Putri Hijau Hospital. This research is an analytic survey with a crosssectional approach. The sample consisted of 100 respondents selected using proportionate stratified random sampling and data were collected through interviews using questionnaires. Data analysis was conducted using the chisquare test. The results showed a significant relationship between biological factors (p<0,05), ergonomic factors (p<0,05), and electrical factors (p<0,05) with the implementation of OHS standards. The implementation of OHS standards, specifically the standards of OHS Risk Management, Hospital Safety and Security, and Fire Prevention and Control has not been optimally applied, as only 35% of nurses implemented the standards properly. This is due to inadequate risk identification, control, and mitigation, as evidenced by the presence of biological agents (viruses, bacteria, fungi, parasites) that can cause infectious diseases, tasks still being performed manually, improper working postures, and the persistent risk of electrocution, fire, or explosion. It is recommended that the hospital strengthen its commitment to OHS implementation by conducting regular training and socialization, imposing sanctions for non-compliance with PPE usage and hand hygiene protocols, maintaining protective biological facilities, providing adequate PPE and vaccination access, ensuring legal protection, addressing ergonomic complaints, supplying ergonomic assistive devices, performing regular electrical system maintenance, providing fire extinguishers and early fire detection systems, and establishing fire response teams in every unit.